2018
DOI: 10.1177/1071100718811632
|View full text |Cite
|
Sign up to set email alerts
|

Superficial Peroneal Nerve Injury Risk During a Semiblind Fasciotomy for Anterior Chronic Exertional Compartment Syndrome of the Leg: An Anatomical and Clinical Study

Abstract: Background: Up to 8% of patients who underwent a fasciotomy for leg anterior chronic exertional compartment syndrome (ant-CECS) report sensory deficits suggestive of iatrogenic superficial peroneal nerve (SPN) injury. In the current study we aimed to thoroughly assess the risk of SPN injury during a semiblind fasciotomy of the anterior compartment using 2 separate approaches. Methods: A modified semiblind fasciotomy of the anterior compartment was performed via a longitudinal 2-cm skin incision 2 cm lateral of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…The technique described by de Bruijn et al is elegant, 2 and very similar to the one we published in 2016, 3 though we started using it at least two decades earlier. Using the simple technical tips described in that article, 3 which de Bruijn et al reproduced in their own cadaveric study, 2 we demonstrated that the neural structures at risk were not injured, and that excellent results can be obtained using routinely available surgical instruments. Other previous studies demonstrated that diagnosis obtained by measurement of intracompartmental pressure (ICP) was necessary to decide the best treatment options and the more indicated surgical technique.…”
mentioning
confidence: 65%
“…The technique described by de Bruijn et al is elegant, 2 and very similar to the one we published in 2016, 3 though we started using it at least two decades earlier. Using the simple technical tips described in that article, 3 which de Bruijn et al reproduced in their own cadaveric study, 2 we demonstrated that the neural structures at risk were not injured, and that excellent results can be obtained using routinely available surgical instruments. Other previous studies demonstrated that diagnosis obtained by measurement of intracompartmental pressure (ICP) was necessary to decide the best treatment options and the more indicated surgical technique.…”
mentioning
confidence: 65%
“…De Bruijn and colleagues 4 investigated the safety of a modified percutaneous fasciotomy technique to decompress the anterior compartment using 9 cadaveric legs and 64 patients. Despite the small numbers, they found no iatrogenic neurovascular injuries.…”
Section: Discussionmentioning
confidence: 99%
“…5,13 The anterior compartment of the leg has been thought to be most commonly affected, and the literature has been heavily focused on techniques to decompress this compartment. 2,4 Recent studies have suggested that deep posterior compartment CECS (dp-CECS) is often overlooked, and its incidence may be higher than anticipated. 22,23 Traditionally, skin and fascial incisions for lower limb fasciotomy have been longitudinal, although some recent studies have demonstrated that transverse incisions may be a suitable alternative.…”
mentioning
confidence: 99%
See 2 more Smart Citations